2014
DOI: 10.1038/ni0214-205a
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: B cell–helper neutrophils stimulate the diversification and production of immunoglobulin in the marginal zone of the spleen

Abstract: In the version of this article initially published, the second affiliation for Stephanie C. Ganal is missing. This author is also affiliated with the Spemann Graduate School of Biology and Medicine, Freiburg, Germany. The error has been corrected in the HTML and PDF versions of the article.Corrigendum: Signaling by Fyn-ADAP via the Carma1-Bcl-10-MAP3K7 signalosome exclusively regulates inflammatory cytokine production in NK cells In the version of this article initially published online, the affiliation of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition, we also demonstrated that the activation of neutrophils by maspin may be B-cell dependent since we showed that mice bearing maspin expressing tumors had elevated expression of tumor-cell reactive and maspin-specific immunoglobulin G (IgG). Although B-cell response is thought to be primarily dependent on CD4 + T-cell interaction, recent studies showed that neutrophils can promote the differentiation and activation of B-cells independently of CD4 + T-cells [37,38]. This was the first evidence demonstrating the function of maspin as an epithelial-specific antigen in cancer disease.…”
Section: A Role Of Maspin In Modulation Of the Host Immunitymentioning
confidence: 91%
“…In addition, we also demonstrated that the activation of neutrophils by maspin may be B-cell dependent since we showed that mice bearing maspin expressing tumors had elevated expression of tumor-cell reactive and maspin-specific immunoglobulin G (IgG). Although B-cell response is thought to be primarily dependent on CD4 + T-cell interaction, recent studies showed that neutrophils can promote the differentiation and activation of B-cells independently of CD4 + T-cells [37,38]. This was the first evidence demonstrating the function of maspin as an epithelial-specific antigen in cancer disease.…”
Section: A Role Of Maspin In Modulation Of the Host Immunitymentioning
confidence: 91%